Responses of ichthyoplankton assemblages to the recent marine heatwave and previous climate fluctuations in several Northeast Pacific marine ecosystems - Nielsen, Jens M (Global change biology, 2021)
© 2020 Her Majesty the Queen in Right of Canada. Reproduced with the permission of the Minister of Fisheries and Oceans Canada. This article has been contributed to by US Government employees and their work is in the public domain in the USA.